Pasti-Sorokin-Tonin actions in the presence of sources - Medina, R. [UNESP]; Berkovits, N. [UNESP] (American Physical Society (APS), 1997)
Pasti, Sorokin, and Tonin have recently constructed manifestly Lorentz-invariant actions for self-dual field strengths and for Maxwell fields with manifest electromagnetic duality. Using the method of Deser et al., we generalize these actions in the presence of sources.